2020
DOI: 10.1016/j.jpainsymman.2020.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Management of COVID-19 Patients—Emergency Palliative Care in Action

Abstract: Context. The COVID-19 pandemic is spreading across the world. Many patients will not be suitable for mechanical ventilation owing to the underlying health conditions, and they will require a conservative approach including palliative care management for their important symptom burden.Objectives. To develop a management plan for patients who are not suitable for mechanical ventilation that is tailored to the stage their COVID-19 disease.Methods. Patients were identified as being stable, unstable, or at the end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
24

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 4 publications
1
77
0
24
Order By: Relevance
“…Moreover, families may be in quarantine or ill themselves. [7] The inability to say goodbye to family before death may increase the risk of complicated grief. [36] When family is allowed to visit, PPE might be needed.…”
Section: Family Members/loved Ones Should Be Invited and Supported (Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, families may be in quarantine or ill themselves. [7] The inability to say goodbye to family before death may increase the risk of complicated grief. [36] When family is allowed to visit, PPE might be needed.…”
Section: Family Members/loved Ones Should Be Invited and Supported (Fmentioning
confidence: 99%
“…because it can be experienced as too distressing. [7] Other authors do advise remote contact between patients in palliative care and family. [37] Results: Almost all experts strongly (80.9%) or conditionally (14.7%) recommend that family members/loved ones should be invited and supported to visit the patient dying with COVID-19 in person.…”
Section: Some Authors Caution Against Virtual Contact Between Familiementioning
confidence: 99%
See 1 more Smart Citation
“…Em relação às temáticas, duas categorias sintetizam os principais aspectos abordados nos estudos: "Estratégias para implementação dos cuidados paliativos no enfrentamento da COVID-19" (17)(18)(19)21,23,25,(27)(28)(29)(30)(31)(32)35,36,(38)(39)(40)(41)(42)44) (19; 63,3%) e "Terapêutica paliativista no contexto da pandemia: desafios e contribuições" (16,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)31,33,34,(36)(37)(38)(39)(40)(41)(43)(44)(45) (24; 80%).…”
Section: Resultsunclassified
“…Much of this knowledge is transferable for people dying with COVID-19 and has been adapted for the pandemic (e.g. Fusi-Schmidhauser et al, 2020). Previous research on end of life care has identified that for a small group of residents dying with or from dementia there is uncertainty about the best ways to manage symptoms, liaise with different people involved in decision making and anticipate resource needs.…”
Section: Expert Reviews (Er)mentioning
confidence: 99%